Feline primary erythrocytosis: a multicentre case series of 18 cats. Issue 12 (December 2018) - Darcy, Hannah; Simpson, Katherine; Gajanayake, Isuru; Seth, Mayank; McGrotty, Yvonne; Szladovits, Balazs; Glanemann, Barbara
Case series summary: A retrospective multicentre case series of feline primary erythrocytosis (PE) was evaluated. The aim was to gain better understanding of disease presentation and progression to guide management and prognostication. Case records were assessed for evidence of increased packed cell volume (PCV; >48%), sufficient investigation to rule out relative and secondary erythrocytosis, and follow-up data for at least 12 months or until death. Eighteen cats were included in the case series. No significant trends in signalment were noted. Seizures and mentation changes were the most common presenting signs (both n = 10). Median PCV was 70% (median total protein concentration of 76 g/l) with no other consistent haematological changes. Sixteen cats survived to discharge. Phlebotomy was performed initially in 15/16 surviving animals and performed after discharge in 10/16. Hydroxyurea was the most common adjunctive therapy, used in 10/16 cats. Of the 16 patients surviving to discharge, 14 patients were still alive at the conclusion of the study (survival time >17 months post-discharge), with the two non-survivors having lived for 5 years or more after diagnosis. PCV, when stabilised, did not correlate with resolution of clinical signs. Relevance and novel information: In contrast to perceptions, feline PE was generally well managed via a combination of phlebotomy and medical therapy, with evidence of prolonged survival times. The use of hydroxyurea enabled cessation or repeat phlebotomies.